Toward an understanding of surface layer formation, growth, and transformation at the glass–fluid interface. (15th May 2018) - Hopf, J.; Eskelsen, J.R.; Chiu, M.; Ievlev, A.V.; Ovchinnikova, O.S.; Leonard, D.; Pierce, E.M.
Abstract: Silicate glass is a metastable and durable solid that has application to a number of energy and environmental challenges (e.g., microelectronics, fiber optics, and nuclear waste storage). If allowed to react with water over time silicate glass develops an altered layer at the solid-fluid interface. In this study, we used borosilicate glass (LAWB45) as a model material to develop a robust understanding of altered layer formation (i.e., amorphous hydrated surface layer and crystalline reaction products). Experiments were conducted at high surface area-to-volume ratio (∼200, 000 m −1 ) and 90 °C in the pressurized unsaturated flow (PUF) apparatus for 1.5-years to facilitate the formation of thick altered layers and allow for the effluent solution chemistry to be monitored continuously. A variety of microscopy techniques were used to characterize reacted grains and suggest the average altered layer thickness is 13.2 ± 8.3 μm with the hydrated and clay layer representing 74.8% and 25.2% of the total altered layer, respectively. The estimate of hydrated layer thickness is within the experimental error of the value estimated from the B release rate data (∼10 ± 1 μm/yr) over the 1.5-year duration. PeakForce® quantitative nanomechanical mapping results suggest the hydrated layer has a modulus that ranges between ∼20 and 40 GPa, which is in the range of porous silica that contains from ∼20 to ∼50% porosity, yet significantly lower than dense silica (∼70–80 GPa). Scanning transmission electron microscopy (STEM) images confirm the presence of pores and an analysis of a higher resolution image provides a qualitative estimate of ≥22% porosity in the hydrated layer with variations in void volume with increasing distance from the unaltered glass. Chemical composition analyses, based on a combination of time-of-flight secondary-ion mass spectrometry (ToF-SIMS), scanning electron microscopy with X-ray energy dispersive spectroscopy (EDS), and STEM-EDS, clearly show that the altered layer is mainly composed of Al, H, Si, and O with the clay layer being enriched in Li, Zn, Fe, and Mg. The amorphous hydrated layer is enriched in Ca, H, and Zr with a minor amount of K. Furthermore, ToF-SIMS results also suggest the B profile is anti-correlated with the H profile in the hydrated layer. Our selected-area electron diffraction results suggest the structure of the hydrated layer closely resembles opal-AG (amorphous gel-like) with an average crystallite size of ∼0.7 nm which is smaller than the critical nucleus for silica nanoparticles (i.e., 1.4–3 nm). These results suggest the hydrated layer is more consistent with a polymeric gel rather than a colloidal gel and is comprised of molecular units (<1 nm in size) that result from the difficult to hydrolyze bonds, such as SiOZr units, during the glass corrosion process. The size of individual particles or molecular units is a function of formation conditions (e.g., pH, ionic strength, nano-confinement, solute composition) in the hydrated layer.